Systemic lupus erythematosus and ANCA-associated vasculites overlap syndrome: A case report and literature review of poliautoimmunity - Gaspar,Ana (2021)
ABSTRACT Systemic lupus erythematosus and ANCA-associated vasculitis overlap syndrome is rare and complex. Moreover, the mechanisms that explain the interaction between these two conditions are still unclear. The authors describe the case of a patient who had myeloperoxidase ANCA-associated vasculitis as the initial diagnosis, with biopsy-proven pauci-immune crescentic glomerulonephritis, attaining complete remission after immunosuppression. Five years later, Systemic Lupus Erythematosus was diagnosed and a second kidney biopsy showed a pattern of lupus nephritis class III. While on immunosuppression treatment, the patient developed a progressive elevation of liver enzymes and was later diagnosed with primary biliary cholangitis. It seems that in this case, the overlap of Systemic Lupus Erythematosus and ANCA-associated vasculitis may be part of a poliautoimmune syndrome suggested by association with a third autoimmune disease.